HGATLink: single-cell gene regulatory network inference via the fusion of heterogeneous graph attention networks and transformer - Yao Sun; Jing Gao (BMC Bioinformatics)
Abstract Background Gene regulatory networks (GRNs) involve complex regulatory relationships between genes and play important roles in the study of various biological systems and diseases. The introduction of single-cell sequencing (scRNA-seq) technology has allowed gene regulation studies to be carried out on specific cell types, providing the opportunity to accurately infer gene regulatory networks. However, the sparsity and noise problems of single-cell sequencing data pose challenges for gene regulatory network inference, and although many gene regulatory network inference methods have been proposed, they often fail to eliminate transitive interactions or do not address multilevel relationships and nonlinear features in the graph data well. Results On the basis of the above limitations, we propose a gene regulatory network inference framework named HGATLink. HGATLink combines the heterogeneous graph attention network and simplified transformer to capture complex interactions effectively between genes in low-dimensional space via matrix decomposition techniques, which not only enhances the ability to model complex heterogeneous graph structures and alleviate transitive interactions, but also effectively captures the long-range dependencies between genes to ensure more accurate prediction. Conclusions Compared with 10 state-of-the-art GRN inference methods on 14 scRNA-seq datasets under two metrics, AUROC and AUPRC, HGATLink shows good stability and accuracy in gene regulatory network inference tasks.